The primary microbial pathogens associated with premature rupture of the membranes in China: A systematic review - Li-nan Zeng; Ling-li Zhang; Jing Shi; Li-ling Gu; Wendie Grogan; Mary M. Gargano; Chen Chen (Elsevier, 2014)
To describe the spectrum of pathogens isolated from Chinese women experiencing premature rupture of the membranes (PROM) and those of their neonates, in order to provide effective management of PROM. We searched Ovid Medline, Chinese Biomedical Literature Database, China National Knowledge Infrastructure, and VIP Database for Chinese Technical Periodicals up to April 2012. The quality of studies was assessed utilizing the Strengthening the Reporting of Observational Studies in Epidemiology Statement. Among the included 36 studies, 11 (30.55%) were deemed to be at Level A, 12 (33.33%) at Level B, three (8.33%) at Level C, and 10 (27.78%) at Level D. Staphylococcus and Escherichia coli were the two primary microorganisms isolated from women with PROM and their infants. Subgroup analysis showed the distribution of microorganisms from the six regions of China varied. Staphylococcus bacteria were resistant to penicillins, except oxacillin, but more sensitive to first- and second-generation cephalosporins. Escherichia were sensitive to first- and second-generation cephalosporins and were more sensitive to aztreonam than cephalosporins. The main pathogens derived from women with PROM and their newborns were Staphylococcus and E. coli, which differs from the pathogens in Western countries. Hence, one might infer that the pathogens involved in PROM should be defined in each region to maximize antibiotic effectiveness. In addition, randomized controlled studies are needed to compare prophylactic use of antibiotics versus use of antibiotics after a positive culture for newborn infants with a history of PROM.